Toyin Falola and African Epistemologies - Bangura, A. author. aut Link
XI, 297 p.
Keywords: While there are five important festschriften on Toyin Falola and his work, this book fulfills the need for a single-authored volume that can be useful as a textbook. I develop clearly articulated rubrics and overarching concepts as the foundational basis for analyzing Falola's work.